Credit Channel and Business Cycle: The Role of Tax Evasion - Bruno Chiarini; Maria Ferrara; Elisabetta Marzano (Center for Economic Studies and ifo Institute (CESifo), 2018)
This paper examines the role of tax evasion in explaining the business cycle in a DSGE model with a financial accelerator. For this purpose, we assume that financially constrained agents are tax evaders, taking advantage of an additional margin of flexibility in coping with adverse shocks. In this setting, we simulate a risk shock that propagates its effects in the credit channel via the financial accelerator mechanism. The results show that tax evasion is pro cyclical and strengthens the effects of the financial accelerator. Unlike the standard literature, in which tax evasion cushions business cycle fluctuations, here we find that it amplifies macroeconomic fluctuations considerably.
Keywords: E32; E44; H26; 330; tax evasion; financial accelerator; business cycle; risk shocks; DSGE modeling